Case Report: C-Reactive Protein Apheresis in a Patient With COVID-19 and Fulminant CRP Increase - Ringel, Jens; Ramlow, Anja; Bock, Christopher; Sheriff, Ahmed (Frontiers in Immunology, 2021)
Background Plasma levels of C-reactive protein (CRP), induced by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) triggering COVID-19, can rise surprisingly high. The increase of the CRP concentration as well as a certain threshold concentration of CRP are indicative of clinical deterioration to artificial ventilation. In COVID-19, virus-induced lung injury and the subsequent massive onset of inflammation often drives pulmonary fibrosis. Fibrosis of the lung usually proceeds as sequela to a severe course of COVID-19 and its consequences only show months later. CRP-mediated complement- and macrophage activation is suspected to be the main driver of pulmonary fibrosis and subsequent organ failure in COVID-19. Recently, CRP apheresis was introduced to selectively remove CRP from human blood plasma. Case Report A 53-year-old, SARS-CoV-2 positive, male patient with the risk factor diabetes type 2 was referred with dyspnea, fever and fulminant increase of CRP. The patient’s lungs already showed a pattern enhancement as an early sign of incipient pneumonia. The oxygen saturation of the blood was ≤ 89%. CRP apheresis using the selective CRP adsorber (PentraSorb® CRP) was started immediately. CRP apheresis was performed via peripheral venous access on 4 successive days. CRP concentrations before CRP apheresis ranged from 47 to 133 mg/l. The removal of CRP was very effective with up to 79% depletion within one apheresis session and 1.2 to 2.14 plasma volumes were processed in each session. No apheresis-associated side effects were observed. It was at no point necessary to transfer the patient to the Intensive Care Unit or to intubate him due to respiratory failure. 10 days after the first positive SARS-CoV-2 test, CRP levels stayed below 20 mg/l and the patient no longer exhibited fever. Fourteen days after the first positive SARS-CoV-2 test, the lungs showed no sign of pneumonia on X-ray. Conclusion This is the first report on CRP apheresis in an early COVID-19 patient with fulminant CRP increase. Despite a poor prognosis due to his diabetes and biomarker profile, the patient was not ventilated, and the onset of pneumonia was reverted.